Penerapan Sanksi Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial Berdasarkan Undang-undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik di Pengadilan Negeri Medan (Studi Kasus Perkara Nomor 248/Pid.Sus/2016/PN.Mdn) - Saragih, Nessia Gresyola; Deliana, Evi; , Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The criminal defamation is a crime caused by the advancement of computer technology. Defamation is a lawless act that attacks the honor or reputation of others. The application of law against defamation offenders is regulated in Law Number 11 Year 2008 on Information and Electronic Transaction Article 45 paragraph (1):